Politik Luar Negeri Malaysia terhadap Indonesia, 1957-1976: Dari Konfrontasi Menuju Kerjasama - Sunarti, Linda (SUSURGALUR, 2014)
IKHTISAR: Dalam perjalanan sejarahnya, hubungan Indonesia dan Malaysia memiliki ciri yang unik. Sebagai tetangga terdekat dan memiliki banyak persamaan dalam berbagai aspek, seperti warisan sejarah, agama, bahasa, dan kebudayaan, hubungan kedua negara tidak selalu berjalan mulus. Makalah ini akan melihat sejarah hubungan Indonesia dan Malaysia yang mengalami pasang-surut. Dalam melihat dinamika hubungan kedua negara, faktor kepentingan nasional dan figur pemimpin merupakan hal yang paling utama. Jika kepentingan nasional dan figur pemimpin kedua negara tersebut berbeda, maka hubungan kedua negara mengalami ketegangan, sebagaimana nampak pada masa pemerintahan Tunku Abdul Rahman di Malaysia (1957-1970) dan pemerintahan Soekarno di Indonesia (1945-1966). Sebaliknya, jika kepentingan nasional dan figur pemimpin kedua negara memiliki kesamaan, maka hubungan kedua negara terjalin dengan baik, sebagaimana nampak pada masa pemerintahan Tun Abdul Razak di Malaysia (1970-1976) dan pemerintahan Soeharto di Indonesia (1966-1998). Dengan demikian, hubungan sejarah dan faktor-faktor kesamaan lainnya tidak serta-merta menjadi pengikat yang kuat, bahkan terkadang menjadi masalah dalam hubungan kedua negara serumpun tersebut, Indonesia dan Malaysia.KATA KUNCI: Hubungan Indonesia-Malaysia, persamaan budaya, figur pemimpin, kepentingan nasional, dan keamanan bersama.ABSTRACT: This paper entitled âMalaysias Foreign Policy toward Indonesia, 1957-1976: From Confrontation toward Cooperationâ. In the course of its history, the relationship between Indonesia and Malaysia has unique characteristics. As the nearest neighbors and has a much similarities in various aspects, such as the legacy of history, religion, language, and culture, relations between the two countries do not always run smoothly. This paper will look at the history of relations between Indonesia and Malaysia, which have ups and downs. In looking at the dynamics of the relations between the two countries, factors of national interests and leading figure are the most important thing. If national interests and leading figure of the two countries are different, the relations between the two countries are strained, as has been seen during the reign of Tunku Abdul Rahman in Malaysia (1957-1970) and the government of Soekarno in Indonesia (1945-1966). Conversely, if the national interests and leading figure of both countries have in common, then, the relations between the two countries are good, as shown at the time of Tun Abdul Razakâs reign in Malaysia (1970-1976) and Soehartoâs government in Indonesia (1966-1998). Thus, the relationship of history and other factors in common does not necessarily become a strong bond, even sometimes to be a problem in the relations between the two brother countries, Indonesia and Malaysia.KEY WORD: Indonesia-Malaysia relations, cultural similarities, leading figure, national interests, and common security.About the Author: Dr. Linda Sunarti adalah Dosen di Program Studi Sejarah, Fakultas Ilmu Pengetahuan Budaya UI (Universitas Indonesia), Kampus UI Depok, Jawa Barat, Indonesia. Untuk kepentingan akademik, penulis bisa dihubungi dengan alamat emel: lindsayrani@yahoo.co.ukHow to cite this article? Sunarti, Linda. (2014). âPolitik Luar Negeri Malaysia terhadap Indonesia, 1957-1976: Dari Konfrontasi Menuju Kerjasamaâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.2(1), Maret, pp.65-80. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808, ISSN 2302-5808. Chronicle of the article: Accepted (January 2, 2014); Revised (February 5, 2014); and Published (Maret 24, 2014).